2016
DOI: 10.1098/rsbl.2015.0733
|View full text |Cite
|
Sign up to set email alerts
|

Flexibility and control of thorax deformation during hawkmoth flight

Abstract: The interaction between neuromuscular systems and body mechanics plays an important role in the production of coordinated movements in animals. Lepidopteran insects move their wings by distortion of the thorax structure via the indirect flight muscles (IFMs), which are activated by neural signals at every stroke. However, how the action of these muscles affects thorax deformation and wing kinematics is poorly understood. We measured the deformation of the dorsal thorax (mesonotum) of tethered flying hawkmoths,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(57 citation statements)
references
References 8 publications
1
53
0
Order By: Relevance
“…Although the exoskeleton is a single, continuous structure, functional specialization of thorax regions decouples P return and P lost . For instance, the wing joint must withstand the high strains necessary for wing movement whereas the scutum may be optimized for spring-like behavior [19]. Because dissipation occurs primarily in the wing joint, the addition of scutum deformations via indirect actuation increases P return by 50% but does does not increase P lost .…”
Section: Strain Coupling Improves Energy Exchange Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Although the exoskeleton is a single, continuous structure, functional specialization of thorax regions decouples P return and P lost . For instance, the wing joint must withstand the high strains necessary for wing movement whereas the scutum may be optimized for spring-like behavior [19]. Because dissipation occurs primarily in the wing joint, the addition of scutum deformations via indirect actuation increases P return by 50% but does does not increase P lost .…”
Section: Strain Coupling Improves Energy Exchange Performancementioning
confidence: 99%
“…In addition, large amplitude heterogeneous strain may concentrate deformations in regions with unfavorable properties for energy exchange (Fig. 2 d) [19]. Thus, interactions between exoskeletal shape and material composition are significant for determining elastic energy exchange capacity.…”
Section: Introductionmentioning
confidence: 99%
“…For a hawkmoth, it was found that flexibility and control of thorax deformation were dependent upon the interaction between neuromuscular systems and body mechanics, and that locally amplified dorsal thorax deformation near the wing-hinge could ensure sufficient wing movement and the phase asymmetry in terms of dorsal thorax oscillations and wing beats [58]. …”
Section: Biomechanics In Insect Flight: Aerodynamics Flight Dynamicsmentioning
confidence: 99%
“…Wing-hinges in insects are flexible structures, which, based on an experimental study of fruit fly saccade [ 31 ], was identified to act like a damped torsional spring and work well to passively resist the wing-tendency to flip in response to aerodynamic and inertial forces, making the pitch control rather simple. For a hawkmoth, it was found that flexibility and control of thorax deformation were dependent upon the interaction between neuromuscular systems and body mechanics, and that locally amplified dorsal thorax deformation near the wing-hinge could ensure sufficient wing movement and the phase asymmetry in terms of dorsal thorax oscillations and wing beats [ 58 ].…”
Section: Biomechanics In Insect Flight: Aerodynamics Flight Dynamicsmentioning
confidence: 99%
“…One potential issue with using these estimates to inform our study, however, is that thorax velocity (from which displacement was estimated via integration) was measured at a single point on the thorax's dorsal surface with laser vibrometry. Ando and Kanzaki measured the dorsal surface of a hawkmoth Agrius convolvuli thorax using a high-speed profilometer found displacements varied significantly along the medial-lateral direction [27]. Thus, it is likely that thorax displacements estimated via single point laser vibrometry are sensitive to the precise location of the measurement.…”
Section: Dynamic Experimental Setupmentioning
confidence: 99%